Relationship Between Job Satisfaction and D Type Personality, Life Satisfaction, and Mental Condition in Intensive Care Nurses - Mahmut Kılıç; Güllü Uslukılıç; Derya Esenkaya; Ökkeş Hakan Miniksar (Association of Nurse Managers, 2021)
Aim: This study aims to determine the relationship between job satisfaction and D-type personality, life satisfaction, and mental state in nurses working in hospital intensive care units. Method: This cross-sectional study was conducted in 2020 among nurses working in intensive care units of hospitals. 294 nurses participated in the study. The data were collected using the Minnesota Job Satisfaction Questionnaire, Type D personality scale (D14), Personal Wellbeing Index-Adult, and Depression Anxiety and Stress Scale. The independent sample t-test, ANOVA, correlation, and multivariate linear regression were used in the data analysis. Results: The life satisfaction of the intensive care unit nurses participating in the study was medium (56.7). It was observed that 53.7% of them had a negatively affecting D-type personality, and 44.2% were social introverted. Nurses' mean scores for depression, anxiety, and stress are low compared to the total score (5.9/21, 5.0/21, and 7.8/21, respectively). Intensive care nurses' intrinsic job satisfaction is higher than their extrinsic job satisfaction. According to the multivariate linear regression analysis, while increased life satisfaction and prolonged working time positively affect intrinsic job satisfaction, anxiety negatively affects it. On the other hand, extrinsic job satisfaction was positively affected by increased life satisfaction and anxiety. In contrast, only the increase in depression was found to be significant in the negative effects. Therefore, total job satisfaction is positively affected by increased life satisfaction, while only negatively affected by depression. Conclusion: While the job satisfaction of intensive care nurses has been positively affected mainly by life satisfaction, no significant relationship was found between job satisfaction and D-type personality and stress.